The illness of public security professionals: a literary approach on the index of the main pathologies that contribute to work absence (Research, Society and Development, 2023)
The article aimed to investigate the main causes of illness among public safety professionals with a focus on social defense, in order to identify problems related to the main pathologies that cause absences and make these professionals sick at their work station, in order to identify solutions to contain this illness. for the improvement of the common good. The methodology was descriptive, qualitative and literary. It was possible to conclude and discover new objectives with the practices of instruments that facilitated the use of technologies in the public security system, the National Public Security Plan and Policy was instituted in December 2018, with the aim of broadly covering the needs of attention to the public safety professional the purpose is to minimize illness in institutions, in the qualitative relation to foster a system that seeks to highlight the reality in current times as well as the means that the State uses to promote defense inside and outside public safety to improve health mental health in the spheres of public security, however, it was possible to see that the main pathologies that cause illness in public security professionals revolve around mental disorders.